Prevalence of Kinesiophobia and Its Correlation with Physiotherapy in Post-Operative Total Knee Arthroplasty (TKA) Patients - a Cross Sectional Study - Pradnya Mahajan, (International Journal of Allied Medical Sciences and Clinical Research, 2020)
Background Kinesiophobia is a condition in which a patient has an excessive, irrational and debilitating fear of physical movement and activity resulting from a feeling of vulnerability to painful injury or re-injury. kinesiophobia had been widely assessed in various conditions including Parkinson’s disease, fibromyalgia, spinal stenosis and low back pain but its prevalence and influence on functional recovery after total knee arthroplasty remains unexplored. Aim To find out the prevalence of kinesiophobia and it’s correlation with physiotherapy in post-operative total knee arthroplasty (TKA) patients. Methods In this cross sectional study, 51 total knee arthoplasty patients were evaluated or assessed for kinesiophobia using Tampa scale of kinesiophobia. Also the patients were divided into 2 groups: Group A- total knee arthroplasty patients who received physiotherapy rehabilitation after total knee arthoplasty and group B- total knee arthroplasty patients who did not received physiotherapy rehabilitation after total knee arthroplasty. Both the groups were evaluated and compared for the presence of kinesiophobia. Results Z test for equality of two proportion was conducted (p< 0.05). Hence there is a significant difference between two ‘p’ values. Conclusion There was presence of kinesiophobia in total knee arhtroplasty patients .There was a significant difference in the level ofkinesiophobiabetween post- operative total knee arthroplasty patients who received physiotherapy and those who did not.